2012
DOI: 10.1590/s1413-86702012000100008
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and sensitivity to antibiotics of bacteria isolated from the lower respiratory tract of ventilated patients hospitalized in intensive care units

Abstract: Objective: This observational study described the characterization of bacteria isolated from the lower respiratory tract of ventilated patients hospitalized in intensive care units.The demonstration of isolated microorganism resistance to antibiotics and a time-trend analysis of infection comparing a 48-month period were also other objectives.Method: Semi-quantitative assays of 1254 samples taken from 741 ventilated patients were performed, while pathogens were identified using the Enterotube II assay and VITE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 22 publications
1
10
1
Order By: Relevance
“…These opportunistic pathogens can also cause superinfections, especially in combination with viral respiratory tract infections in hospitalized patients. However, even patients without underlying diseases and in all age groups may be at the risk of co-infections as well [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…These opportunistic pathogens can also cause superinfections, especially in combination with viral respiratory tract infections in hospitalized patients. However, even patients without underlying diseases and in all age groups may be at the risk of co-infections as well [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…Colistin initially binds to the lipid A moiety of lipopolysaccharide (LPS), resulting in destabilization of the Gram-negative outer membrane (4). Alarmingly, as the use of colistin has increased, so have reports of colistin-resistant A. baumannii strains (5)(6)(7)(8)(9)(10). Previously, we have shown that A. baumannii can become resistant to colistin via mutations in the lipid A biosynthesis genes lpxA, lpxC, and lpxD, leading to the complete absence of LPS from the outer membrane (11,12); significantly, LPS loss has been observed in clinical isolates (11).…”
mentioning
confidence: 99%
“…are the most frequently detected causative agents of NIs 9 . In hospitalized patients with viral pneumonias, these opportunistic pathogens can cause superinfections not only in patients with serious underlying disease but also in patients without underlying diseases and in all age group 10,11 .…”
Section: Discussionmentioning
confidence: 99%
“…In accordance with local multidrug resistance (MDR) surveillance policy, all of the MDR bacteria isolated from blood cultures are routinely collected and stored at -80°C. The genetic relationships of the vancomycin-resistant Enteroccoccus species strains isolated from COVID-19 patients were explored by means of automated repetitive extragenic palindromic polymerase chain reaction (DiversiLab Enterococcus kit, bioMérieux) 9,10 . The amplified fragments were separated by means of capillary electrophoresis and their band patterns were compared using an Agilent 2100 Bioanalyzer (Agilent Technologies, Palo Alto, CA).…”
Section: Participantsmentioning
confidence: 99%